2018
DOI: 10.1186/s12970-018-0263-6
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic impact of protein feeding prior to moderate-intensity treadmill exercise in a fasted state: a pilot study

Abstract: BackgroundAugmenting fat oxidation is a primary goal of fitness enthusiasts and individuals desiring to improve their body composition. Performing aerobic exercise while fasted continues to be a popular strategy to achieve this outcome, yet little research has examined how nutritional manipulations influence energy expenditure and/or fat oxidation during and after exercise. Initial research has indicated that pre-exercise protein feeding may facilitate fat oxidation while minimizing protein degradation during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 47 publications
6
19
0
Order By: Relevance
“…Importantly, EE in the energy drink condition was found to be approximately 0.77 kcal·min − 1 higher than placebo during the post-beverage time period, and approximately 0.37 kcal·min − 1 higher than placebo during the post-exercise time period. These results align with the findings of previous studies which reported significant elevations in EE following consumption of caffeine-containing energy drinks [ 11 13 ] as well as those which administered supplemental protein prior to exercise [ 15 17 ]. Several physiological mechanisms are responsible for these results.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Importantly, EE in the energy drink condition was found to be approximately 0.77 kcal·min − 1 higher than placebo during the post-beverage time period, and approximately 0.37 kcal·min − 1 higher than placebo during the post-exercise time period. These results align with the findings of previous studies which reported significant elevations in EE following consumption of caffeine-containing energy drinks [ 11 13 ] as well as those which administered supplemental protein prior to exercise [ 15 17 ]. Several physiological mechanisms are responsible for these results.…”
Section: Discussionsupporting
confidence: 91%
“…A variety of investigations have demonstrated that the consumption of caffeine-containing energy drinks may acutely increase metabolic rate [11][12][13], which could potentially result in preferential changes in body composition over time with prolonged use [14]. Similar short-term metabolic effects have also been noted following the acute consumption of supplemental protein prior to an exercise session [15][16][17]. For example, Wingfield and colleagues [16] examined the metabolic impact of supplemental protein ingestion prior to aerobic exercise, high-intensity interval training, and resistance training.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In line with our findings, others have reported a protein-rich pre-exercise meal increased fat oxidation during moderate-intensity exercise compared with a CHO-rich meal [ 34 ], and there were no differences in fat oxidation when consuming whey protein before and during steady-state cycling compared with a placebo (fasted) trial [ 7 ]. Similar levels of fat oxidation between fasted and protein-fed exercise have also been reported during cycling between 58%–86% VO 2max [ 10 ], running at 55%–60% heart rate reserve [ 9 ], and cycling at ~50% VO 2max in a glycogen-depleted state [ 8 ]. A primary reason endurance athletes perform fasted-state training is a desire to increase fat oxidation during exercise [ 6 ], and our findings provide further evidence supporting the use of both pre-exercise protein ingestion and fasted-state training to increase fat oxidation during low-intensity exercise compared with a CHO-rich breakfast, which likely impairs fat oxidation.…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, pre-exercise protein ingestion may be an alternative to performing fasted-state training that could reduce hunger while maintaining high levels of fat oxidation. Additional research is needed to better understand differences in substrate oxidation between CHO-fed, protein-fed, and fasted-state training, as previous studies using pre-exercise protein ingestion have either not had a CHO control group [ 7 , 8 ], performed extended exercise at a single intensity [ 7 , 8 , 9 ], or provided very large (>1000 kcal) pre-exercise meals [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%